WORK MOTIVATION OF EMPLOYEES AT THE EDUCATION AND CULTURE OFFICE OF AGAM REGENCY - Meta Afra Niska; Yulianto Santoso; Hadiyanto Hadiyanto; Merika Setiawati (STKIP Pesisir Selatan, 2026)
Objective: This study aims to determine the level of employee work motivation in terms of goal-oriented drive, work enthusiasm, initiative and creativity, responsibility, and performance recognition. Methods: This study employed a quantitative approach using a descriptive method. The research population consisted of 79 employees, and all of them were selected as the sample using the total sampling technique. Data were collected through a Likert-scale questionnaire and analyzed by calculating the mean score. Results: The results showed that the work motivation of employees at the Agam Regency Education and Culture Office was in the high category, with an average score of 4.42. Specifically, the indicator of goal-oriented drive obtained a score of 4.51, work enthusiasm 4.48, initiative and creativity 4.43, responsibility 4.53, and performance recognition 4.15, all of which were categorized as high. These findings imply that employee work motivation is generally in a good condition; however, the aspect of performance recognition still needs to be improved through more optimal appreciation and reward systems to further enhance employee motivation and performance. Novelty: This study provides a comprehensive overview of employee work motivation at the Agam Regency Education and Culture Office based on five key indicators, namely goal-oriented drive, work enthusiasm, initiative and creativity, responsibility, and performance recognition.